Design considerations for application selection and control in multi-user public displays - Taivan, Constantin (2013)
Urban spaces are increasingly embedded with various types of public digital displays. Many of these displays can be subject to multi-user interactions and support a broad range of applications. A fundamental implication emerging from the interactive nature of those applications is that users should have access to appropriate selection and control techniques that would allow them to drive the way applications are shown and used in the respective environment. Such techniques should enable each user to reason and express intentions about the system behavior, while also dealing with concurrent requests from multiple users in a way that is fair and clear. In this study, we aim to inform the definition of novel techniques for application selection and control in pervasive display environments that can address the above challenges. Drawing inspiration from traditional GUI interaction concepts we developed and deployed a public display system that supports multiple applications and is able to receive explicit content presentation requests from multiple viewers. Based on the experiment observations and interviews with the participants, we reached a set of design considerations for future pervasive displays environments that are open to third party applications providers and allow the audience to influence content presentation.